2022
DOI: 10.3389/fphar.2022.885075
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Long Non-Coding RNAs in Esophageal Cancer: Functions in Tumorigenesis and Clinical Implications

Abstract: Esophageal cancer (EC) is one of the most common malignancies of digestive tracts with poor five-year survival rate. Hence, it is very significant to further investigate the occurrence and development mechanism of esophageal cancer, find more effective biomarkers and promote early diagnosis and effective treatment. Long non-coding RNAs (lncRNAs) are generally defined as non-protein-coding RNAs with more than 200 nucleotides in length. Existing researches have shown that lncRNAs could act as sponges, guides, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 185 publications
0
5
0
Order By: Relevance
“…Malignant transformation requires alteration of signaling flow and disruption of intracellular homeostasis. Numerous studies have demonstrated that lncRNAs may lie at the heart of cellular information flux, as they can act as decoys, guides or scaffolds for proteins and other noncoding RNAs [ 7 ]. Overexpression of LINC00858 has been reported to promote proliferation and migration of non-small cell lung cancer and colorectal cancer by acting as a competing endogenous RNA [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant transformation requires alteration of signaling flow and disruption of intracellular homeostasis. Numerous studies have demonstrated that lncRNAs may lie at the heart of cellular information flux, as they can act as decoys, guides or scaffolds for proteins and other noncoding RNAs [ 7 ]. Overexpression of LINC00858 has been reported to promote proliferation and migration of non-small cell lung cancer and colorectal cancer by acting as a competing endogenous RNA [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, tumor metastasis is a multistep process that involves both genetic and epigenetic alterations [ 6 ]. As newly discovered epigenetic regulators, long noncoding RNAs (lncRNAs) have become hot topics in cancer research in recent years [ 7 ], and aberrant expression or dysfunction of lncRNAs is closely related to GC development and metastasis [ 8 , 9 ]. For example, Sun TT et al reported that GClnc1 affects proliferation, invasiveness, and metastasis by acting as a scaffold to recruit the WDR5 and KAT2A complex and modify the transcription of target genes in GC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA is bound to DNA or proteins; decoy molecules inhibit the transcription of downstream genes while guide molecules enhance the transcription. Backbone molecules are scaffold molecules for protein complexes to form nucleic acid-protein complexes involved in epigenetic functions ( Han et al, 2022 ; Nadhan et al, 2022 ).…”
Section: Lncrnasmentioning
confidence: 99%
“…Examining the roles of lncRNAs in cancer also involves recognizing differential expression patterns between cancer types and stages. Several lncRNAs, including Hox transcript antisense RNA ( HOTAIR ) and non‐coding RNA activated by DNA damage ( NORAD ), have been identified as promising biomarkers in the prognosis of esophageal cancer due to their elevated expression levels 7 . HOTAIR is well‐known for being oncogenic, and its high expression in several cancer types is related to chemotherapy resistance 8 .…”
Section: Figurementioning
confidence: 99%
“…Several lncRNAs, including Hox transcript antisense RNA (HOTAIR) and non-coding RNA activated by DNA damage (NORAD), have been identified as promising biomarkers in the prognosis of esophageal cancer due to their elevated expression levels. 7 HOTAIR is well-known for being oncogenic, and its high expression in several cancer types is related to chemotherapy resistance. 8 Determining the prognosis associated with the up-or down-regulation of each lncRNA would greatly benefit precision medicine, as it would facilitate the customization of treatment plans and thereby enhance the effectiveness of treatment plans to help reduce tumour recurrence.…”
mentioning
confidence: 99%